The design of Thermoplastic packaging and products maker for Small and Medium Enterprises (SMEs) in Indonesia - Dian Cahyadi; Lanta L; Nurabdiansyah; Muhammad Farid (Center for Humanities and Innovation Studies, 2019)
The production technology of packaging and other products based on plastic material is not as complicated as many people think. This research is a study to find the proper method to use in the design of packaging and plastics maker tools. The product is dedicated to (Small and Medium Enterprises (SMEs) in Indonesia to encourage them to produce products with attractive packaging. By the creation of this toolmaker is also expected to be potentially marketable for industrial development based on the use of materials from plastic. The literature study method is used to collect all pertinent information about appropriate methods, systems, and technical molding that can be used to form the basis of application of design materials. The methods can be applied to the design plan of packaging equipment and plastic products. This research is based the basic concepts of engineering principles of equipment consisting of heating and forming process using vacuum cleaner machine tool that is easily obtained and prepare the box facilities that can be obtained around our environment. In addition, by understanding the engineering principles of equipment, vacuum forming can be done. This research shows that using Thermoplastic can produce not only the packaging that is the specific purpose of this research activity, but also has the potential market space to produce a wide range of other creative products.